(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2017)
This paper describes a phenomenological study of the experiences of women who binge drink. The research analysis was conducted with SEA (Structural Existential Analysis) as a research heuristic. The research was carried out with eight women who regularly binge drink on nights out. All participants were professional women in the age group 25–55 whose drinking falls outside parameters generally defined as problematic.